2007
DOI: 10.4067/s0716-10182007000300005
|View full text |Cite
|
Sign up to set email alerts
|

Aislamiento e identificación de especies pertenecientes a los géneros Aeromonas, Vibrio y Plesiomonas procedentes de muestras extra-intestinales en Cuba

Abstract: Introducciónos bacilos gramnegativos, anaerobios facultativos, oxidasa positiva, pertenecen a los géneros Aeromonas, Vibrio y Plesiomonas, ubicados taxonómicamente en las familias Aeromonadaceae, Vibrionaceae y Enterobacteriaceae, respectivamente 1 .Es reconocido el incremento de las infecciones por los microorganismos pertenecientes a los mencionados géneros, como agentes etiológicos de procesos infecciosos en órganos y sistemas vitales para el organismo, comprometiendo en ocasiones la vida del paciente 2-4 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Large numbers of (29%) endophthalmitis patients were reported to have mixed infection with V. fluvialis (Hassan et al, 1992). A report from Cuba showed that V. fluvialis was one of the predominantly identified pathogens from different extraintestinal samples (Cabrera et al, 2007). Cases of bacteremia with diarrhea (Lai et al, 2006) hemorrhagic cellulitis and cerebritis (Huang and Hsu, 2005), peritonitis (Ratnaraja et al, 2005) have also been reported.…”
Section: Other Infectionsmentioning
confidence: 99%
“…Large numbers of (29%) endophthalmitis patients were reported to have mixed infection with V. fluvialis (Hassan et al, 1992). A report from Cuba showed that V. fluvialis was one of the predominantly identified pathogens from different extraintestinal samples (Cabrera et al, 2007). Cases of bacteremia with diarrhea (Lai et al, 2006) hemorrhagic cellulitis and cerebritis (Huang and Hsu, 2005), peritonitis (Ratnaraja et al, 2005) have also been reported.…”
Section: Other Infectionsmentioning
confidence: 99%